Reducing Postoperative Abdominal Bulge Following Deep Inferior Epigastric Perforator Flap Breast Reconstruction with Onlay Monofilament Poly-4-Hydroxybutyrate Biosynthetic Mesh - Wormer, Blair A.; Clavin, Nicholas W.; Lefaivre, Jean-Francois; Korn, Jason M.; Teng, Edward; Aukskalnis, Anthony S.; Robinson, J. Michael (Journal of Reconstructive Microsurgery, 2017)
Background The purpose of this study was to evaluate the use of a biosynthetic mesh onlay on reducing postoperative abdominal bulge following deep inferior epigastric perforator (DIEP) flap breast reconstruction.Methods All patients undergoing DIEP reconstructions from January, 2010 to January, 2014 at a tertiary center were reviewed. Patients were divided into two groups for comparison based on whether a biosynthetic mesh onlay (Phasix [monofilament poly-4-hydroxybutyrate], Bard Inc., Warwick, RI) was used for reinforcement of the anterior rectus fascia. Rates of postoperative abdominal bulge were compared between the groups utilizing standard statistical methods.Results During the study period, 319 patients underwent 553 DIEP reconstructions, 160 (50.2%) used mesh and 159 (49.8%) did not (nonmesh). The mean follow-up was 16.4 ± 11.1 months. There was no difference in age (49 ± 9.3 years), current tobacco use, diabetes, or mean body mass index (BMI, 29.4 ± 4.4) between the mesh and nonmesh groups (p > 0.05); however, there was a higher proportion of obese patients (BMI > 30) in the mesh group (45.0 vs. 33.3%; p = 0.03). Abdominal bulge rate following DIEP with mesh was lower than the nonmesh group (0 vs. 5.0%; p = 0.004). In the entire sample, 234 (73.4%) underwent bilateral DIEP and 85 (26.6%) underwent unilateral DIEP. In unilateral DIEP patients, the bulge rate was similar between the mesh and nonmesh groups (0 vs. 4.4%; p > 0.05); however, in bilateral DIEP patients, the bulge rate was lower in the mesh group compared with a nonmesh group (0 vs. 5.5%; p = 0.008).Conclusion Reinforcement of the anterior rectus with an onlay monofilament poly-4-hydroxybutyrate biosynthetic mesh may reduce the risk of postoperative bulge rate in patients undergoing DIEP reconstruction.
Keywords: DIEP; biosynthetic mesh; donor-site morbidity